The cost savings of the rural accelerated chest pain pathway for low-risk chest pain in rural general practice: a cost minimisation analysis - Martin Than; Talis Liepins; John W. Pickering; Michelle Smith; Tim Stokes; Garry Nixon; Rory Miller (CSIRO Publishing, 2023)
Introduction The rural accelerated chest pain pathway (RACPP) has been shown to safely reduce the number of transfers to hospital for patients who present with chest pain to rural general practice. Aim This study aimed to estimate the costs associated with assessing patients with low-risk chest pain using the RACPP in rural general practice compared with transporting such patients to a distant emergency department (ED). Methods This was a retrospective cost minimisation analysis. All patients with low-risk chest pain that were assessed in New Zealand (NZ) rural general practice using the RACPP between 1 June 2018 and 31 December 2019 were asked to participate. The costs incurred by patients were determined by an online survey. Patients were also asked to estimate the costs if they would have been transferred to ED. System costs were obtained from the relevant healthcare organisations. The main outcome measure was the total cost for patients who present with low-risk chest pain. Results In total, 15 patients (22.7% response rate) responded to the survey. Using the RACPP in general practice resulted in a median cost saving of NZ$1184 (95% CI: $1111 to $1468) compared with transferring the same patient to ED. Discussion Although limited by low enrolment, this study suggests that there are significant savings if the RACPP is used to assess patients with low-risk chest pain in rural NZ general practice.